The Role of The Republic of Uzbekistan in Developing Cooperation with Countries within the Framework of The Commonwealth of Independent States in The XXI Century - Farkhod Ya. Duschanov; Doniyor D. Kutliev (Genius Journals, 2023)
This article discusses the cooperation relations of the CIS countries and development strategies of Uzbekistan within the CIS
Keywords: CIS; state; cooperation; development